(3JWHjbGJ Ydj cjajI JUeje hEOGQI ehbYc Ydj GdEfJQfJs ((3GdbGgQIs Pc Lab, 2004)
(3aj gPg GdeLehYI GdJYdjejI Sha fJYQa Ydj cjajI Yed ehbY hjH eJcGed HGSJNOGe eLehYI eJNUUI ef GdHQGeL hgj HQfGeL (BAdobe Photoshop cs(3, hHQfGeL (BMacromedia Flash 8(3, hHQfGeL(BFireworks MX 2004(3,HGdEVGaI Edj HYV GdCchGOs
1 2
Keywords: (3GdEfJQfJs -- (3ehGO SeYjI hHUQjIs; (3GdMGSHGJ GdEdcJQhfjIs -- (3HQGeLs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjGs -- (3cHGQs -- (3ehGO SeYjI hHUQjIs